Utilizing the Central Sulawesi Museum as a Resource for History Learning in Grade 11 at Palu State High School 2 - Ulul Asmi; Hasan Hasan; Charles Kapile; Idrus Rore (Journal of Educational Sciences, 2026)
Museums are important institutions for preserving history and culture and can serve as valuable learning resources. However, their use in schools remains limited due to the dominance of textbook-based instruction and students’ low interest in learning history. Therefore, more contextual and interactive learning approaches are needed to make historical learning more meaningful. This study aims to analyze the utilization of the Central Sulawesi Museum (UPT Museum Sulawesi Tengah) as a history learning resource at Palu State High School 2. The research employed a qualitative method, with data collected through observation, interviews, and documentation. The participants included history teachers, eleventh-grade students, and museum guides. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that museum-based learning is implemented systematically through activities conducted before, during, and after visits. The museum’s collections are relevant to the history curriculum, particularly topics on prehistory, enabling students to understand historical material more concretely. Furthermore, museum visits increase students’ interest, motivation, and enthusiasm for learning history. Despite challenges such as limited transportation, facilities, human resources, and interactive learning materials, the Central Sulawesi Museum remains an effective and meaningful resource for supporting history education in schools.